Kajian Normatif Tentang Tindak Pidana Pencemaran Nama Baik Di Dunia Maya - Yasmirah Mandasari Saragih; Muhammad Ridwan Lubis (Universitas Merdeka Madiun, 2019)
The purpose of this study was to determine how the validity or legal domicile Electronic Information and Electronic Documents as evidence in the criminal act of defamation in cyberspace as well as to determine the application of the law on criminal acts of defamation in cyberspace. By using the method of normative legal research, it can be concluded that: 1. In the event of the power and value of the evidence, the evidence provided for in Article 184 Criminal Procedure Code, which is the strength of evidence of electronic evidence is free (volledig bewijskracht) and is not binding or specify ( beslissende bewijskracht). Probative value of all evidence based on the judge's assessment. Setting electronic evidence in UU ITE regulated in Chapter III of Information, Document and Electronic Signature, as well as Article 44 of Law ITE. Article 5 (1) of the EIT set explicitly that information or electronic documents and / or printouts are valid evidence. Furthermore, Article 5 (2) states that